Interrelationships of the hidden economy and some visible segments of the labour market - Mária Lackó (Hungarian Academy of Sciences, Institute of Economics, 2007)
Since there are no broadly accepted macro-level estimations for the size of the hidden economy, the interrelationships of the hidden economy with different segments of the labor market have to be approached in a number of different ways. In our cross-country analysis, in parts 2 and 3 we use indirect estimations of the hidden economy and show that the size of the hidden economy and the size of self-employment can be explained by similar explanatory variables, tax rates and corruption being prominent among them. In part 4 we set up and quantify a model to analyze the interrelationships among the hidden economy and the pools of self-employed and non-employed people. For this model we use a specific direct indicator of the hidden economy, the concealed consumption share which is derived from the notion of the non-observed economy used by statistical agencies. We show that the size of this part of the hidden economy is determined by the tax rate related to the consumption and the level of corruption. We also demonstrate that the concealed consumption share plays an important role in the determination of the size of various segments of the labor market, while the developments of these segments also have their impact on this specific part of the hidden economy.
Keywords: H26; D73; J2; E26; 330; Hidden economy; labor market; taxation; corruption; Informelle Wirtschaft; Schattenwirtschaft; Arbeitsmarkt; Steuer; Korruption; Welt